Peculiar spin frequency and radio profile evolution of PSR J1119−6127 following magnetar-like X-ray bursts. Issue 3 (1st August 2018) - Dai, S; Johnston, S; Weltevrede, P; Kerr, M; Burgay, M; Esposito, P; Israel, G; Possenti, A; Rea, N; Sarkissian, J
ABSTRACT: We present the spin frequency and profile evolution of the radio pulsar J1119 − 6127 following magnetar-like X-ray bursts from the system in 2016 July. Using data from the Parkes radio telescope, we observe a smooth and fast spin-down process subsequent to the X-ray bursts resulting in a net change in the pulsar rotational frequency of Δν ≈ −4 × 10 −4 Hz. During the transition, a net spin-down rate increase of Δ ν ≈ -1× 10^-10 Hz s −1 is observed, followed by a return of ν to its original value. In addition, the radio pulsations disappeared after the X-ray bursts and reappeared about two weeks later with the flux density at 1.4 GHz increased by a factor of 5. The flux density then decreased and undershot the normal flux density followed by a slow recovery back to normal. The pulsar's integrated profile underwent dramatic and short-term changes in total intensity, polarization, and position angle. Despite the complex evolution, we observe correlations between the spin-down rate, pulse profile shape, and radio flux density. Strong single pulses have been detected after the X-ray bursts with their energy distributions evolving with time. The peculiar but smooth spin frequency evolution of PSR J1119−6127 accompanied by systematic pulse profile and flux density changes are most likely to be a result of either reconfiguration of the surface magnetic fields or particle winds triggered by the X-ray bursts. The recovery of spin-down rate and pulse profile to normal provides us the best case to study the connection between high magnetic-field pulsars and magnetars.